To Summarize and Analyze the Epidemiological Characteristics and Prognostic Risk Factors of Patients with Pelvic Fracture Complicated with Perineal Injury. (30th March 2022) - Li, Wen; Du, Shasha; Guo, Houcai; Han, Xuan; Huang, Tao
Abstract : This study is aimed at summarizing and analyzing the epidemiological characteristics and prognostic risk factors of patients with a pelvic fracture with perineal injury. The clinical data of 153 patients with pelvic fracture with perineal injury treated in our hospital from January 2012 to June 2021 were analyzed retrospectively. The data of sex, age, injury mechanism, pelvic fracture type, shock index (SI), perineal wound depth, concomitant injury, total hospital stay, and death were collected by the electronic medical record system. Among the 153 patients, there were 94 males and 59 females, with an average age of (43.2 ± 16.8) years. The cases were mainly concentrated into two age groups: 20–29 years old and 50–59 years old. In a year, pelvic fractures were mainly concentrated in 1–2 months and 11–12 months. In terms of injury time, there were mainly two periods of time in a day: 10 : 00～12 : 00 and 15 : 00～18 : 00. The MOTS-RTS scores of the patients in the undead group and the dead group were (7.12 ± 1.52), (2.69 ± 0.96), ISS scores were (27.36 ± 15.84), (61.32 ± 7.08), GCS scores were (12.84 ± 3.69), (4.13 ± 1.25), APACH II scores were (12.87 ± 8.84), (32.41 ± 6.98), and SOFA scores were (6.68 ± 5.87), (17.12 ± 3.12). The MOTS-RTS and GCS scores of the nondeath group were significantly higher, while the ISS score, APACH II score, SOFA score, and shock index were significantly lower. The overall mortality rate of 153 patients was 13.7%. The average area of perineal trauma in undead and dead patients was (54.5 ± 113.52) cm 2 and (262.63 ± 300.84) cm 2, respectively. The average depth of perineal trauma was (9.63 ± 7.22) cm and (16.23 ± 10.13) cm, respectively. The larger the area of perineal injury and the deeper the depth of perineal trauma, the worse their prognosis. Cox multivariate analysis showed that complications, MOTS-RTS score, ISS score, GCS score, perineal trauma area, and perineal trauma depth were independent risk factors affecting the prognosis of patients with pelvic fracture with perineal injury. Most of the patients with pelvic fracture complicated with perineal injury are 20–29 years old and 50–59 years old. The more serious the perineal injury is, the higher the mortality is. The main causes of death are refractory hemorrhagic shock and infection.